PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA KELAS X DI SMK WIRA BUANA BEKASI - Muhamad Dafa Laksana (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to determine the effect of Entrepreneurship Education on Entrepreneurial Interest in Grade 10 Students at Wira Buana Vocational High School, Bekasi. To obtain data, the variables of Economic Education and Entrepreneurial Interest were used in the form of a Likert scale. This study used a quantitative approach, with data sources obtained from a sample of 30 students at Wira Buana Vocational High School. The data analysis technique used was Simple Linear Regression using the SPSS 22 application. Based on the results of the linearity test output conducted using SPSS 22, the data above shows a significance value of Deviation from Linearity of 0.201 > 0.05 and a calculated F value contained in the Deviation from Linearity of 1.686 and an F table value of 2.798 (The F table value is obtained from a = 0.05; df1 = 18; df2 = 10 is 2.798) with a significance of 0.05, the F table is found to be 2.798, because 1.686 < 2.798, it is concluded that there is a linear relationship between the Entrepreneurship Education variable (X) and the Entrepreneurial Interest variable (Y) is linear. Based on the Determination Test results table above, the Adjusted R Square (coefficient of determination) is 0.982, meaning the influence of the entrepreneurship education variable (X) on entrepreneurial interest (Y) is 98,2%.